Utilização intracoágulo de espuma fibrinolítica - preparação, caracterização e atividade in vitro de uma espuma de estreptoquinase e proposta de uma nova abordagem terapêutica - Farret Neto, Abdo (2014)
Foam was developed as a novel vehicle for streptokinase with the purpose of increasing the contact time and area between the fibrinolytic and the target thrombus, which would lead to a greater therapeutic efficacy at lower doses, decreasing the drug s potential to cause bleeding. Fibrinolytic foams were prepared using CO2 and human albumin (at different v:v ratios), as the gas and liquid phases, respectively, and streptokinase at a low total dose (100,000 IU) was used as fibrinolytic agent conveyed in 1 mL of foam and in isotonic saline solution. The foams were characterized as foam stability and apparent viscosity. The thrombolytic effect of the streptokinase foam was determined in vitro as thrombus lysis and the results were compared to those of a fibrinolytic solution (prepared using the same dose of streptokinase) and foam without the fibrinolytic. In vitro tests were conducted using fresh clots were weighed and placed in test tubes kept at 37 ° C. All the samples were injected intrathrombus using a multiperforated catheter. The results showed that both foam stability and apparent viscosity increased with the increase in the CO2:albumin solution ratio and therefore, the ratio of 3:1 was used for the incorporation of streptokinase. The results of thrombus lysis showed that the streptokinase foam presented the highest thrombolytic activity (44.78 ± 9.97%) when compared to those of the streptokinase solution (32.07 ± 3.41%) and the foam without the drug (19.2 ± 7.19%). We conclude that fibrinolytic foam showed statistically significant results regarding the enhancement of the lytic activity of streptokinase compared to the effect of the prepared saline solution, thus it can be a promising alternative in the treatment of thrombosis. However, in vivo studies are needed in order to corroborate the results obtained in vitro